Determination of thermo-optic coefficient, refractive index, optical dispersion and group velocity parameters of an organic thin film - Yakuphanoğlu, Fahrettin; Arslan, M. (Elsevier Science Bv, 2007)
The optical parameters such as thermo-optic coefficient (TOC), refractive index, optical dispersion and group velocity in 7,7,8,8-tetracyanoquinod dimethane (B6-TCNQ) charge transfer complex thin film have been investigated. The obtained results show that the group velocity decreases with annealing temperatures. The thermo-optic coefficient of the film, dn/dT, was calculated and is strongly dependent of temperature and wavelength. The organic film exhibits a negative dn/dT. A difference between group and phase velocities is observed due to the optical dispersion. The temperature dependence of optical band gap (E-g) of the film was found to vary from 2.03 to 1.83eV, i.e., the optical band gap decreases with increasing annealing temperatures. The rate of change of optical band gap with temperature for the films was found to be -1.65 x 10(-3) eV/degrees C. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: thin film; optical band; refractive index dispersion; heat treatment